Survival Strategies of Fishermen in Bahodopi Amid Ecological Changes in Mining Areas - Junaidi, M.; Naping, Hamka; Hijjang, Pawennari; Yahya, Yahya (Journal La Sociale, 2024)
This research explores the perspective of human adaptation as a cultural response to ecological change. Ecological and economic pressures drive humans to consciously choose and take advantage of opportunities in their ecological environment. The Bahodopi mining area is the context to explain human adaptation to these ecological changes. Nickel mining results in changes in the ecological environment that have an impact on people's lives. The destruction of the ecosystem affects the lives of people in mining areas such as fishermen in Bahodopi. Coastal fishermen in Bahodopi take advantage of the potential of marine resources by catching fish to meet their living needs before the mine. The marine and coastal environment as a habitat for fish is polluted by mining waste such as factory waste, other liquid waste, and mud materials due to the excavation of materials upstream damaging fish habitats. This condition is not favorable for fishermen because they cannot meet the economic needs of their families. Fishermen's economic activities have stopped because their catches have decreased along with the development of mining activities and the destruction of marine ecosystems. The Bahodopi mining area provides job opportunities for residents to become employees, entrepreneurs, service businesses, and the informal sector along with the number of mining workers. Utilization of natural resource potential such as being a stone breaker, wage labor in pepper gardens, and planting vegetables in the yard. Fishing families take advantage of the potential of other resources and economic opportunities as a form of adaptation to ecological changes.